Chromobox protein homolog 7 suppresses the stem-like phenotype of glioblastoma cells by regulating the myosin heavy chain 9-NF-κB signaling pathway - Kaixiang Ni; Yuankun Liu; Pinggang DI; Lu Wang; Hui Huang; R. M. Damian Holsinger; Karrie Mei-Yee Kiang; Jiantong Jiao (Cell Death Discovery)
Abstract Cancer stem cells (CSCs) are significant factors in the treatment resistance and recurrence of glioblastoma. Chromobox protein homolog 7 (CBX7) can inhibit the progression of various tumors, but its impact on the stem cell-like properties of glioblastoma cells remains unclear. Clinically, low levels of CBX7 are associated with poor prognosis and increased distant metastasis in glioblastoma patients, and this low expression is caused by methylation of the CBX7 promoter. Our current research indicates that CBX7 plays a key role in suppressing the stem-like phenotype of glioblastoma. In this study, through bioinformatics analysis, we found that CBX7 is the most significantly downregulated member of the CBX family in glioblastoma and is closely associated with the stem-like phenotype of glioblastoma cells. We show that CBX7 promotes the degradation of myosin heavy chain 9 (MYH9) protein through the ubiquitin-proteasome pathway via the polycomb repressive complex 1 (PRC1) and suppresses the stem-like phenotype of glioblastoma cells by inhibiting the nuclear factor kappa-B (NF-κB) signaling pathway. Furthermore, overexpression of MYH9 in glioblastoma cells reverses the inhibitory effects of CBX7 on migration, proliferation, invasion, and stemness of glioblastoma cells. In summary, CBX7 acts as a tumor suppressor by inhibiting the stem cell-like characteristics of glioblastoma. The CBX7-MYH9-NF-κB signaling axis may serve as a potential therapeutic target for glioblastoma.